Bhimal (Grewia optiva): A miracle tree with the potential to improve livelihood security of himalayan farming communities - Mondal, Tilak; Laskar, Namrata; Mridha, Nilimesh; Singha, Atul; Das, Avijit; Shakyawar, D. B. (Indian Farming, 2025)
Bhimal is widely distributed in the sub-Himalayan region, especially Uttarakhand. It is known for its versatile use, such as durable fibre, nutritious fodder, fuelwood, and medicinal products. It also holds cultural and religious importance and is significant in local rituals and traditions. Bhimal serves as a vital component in rural livelihood of Himalayan farming communities. It can grow in challenging Himalayan terrains and can prevent soil erosion and improve soil fertility. With its adaptability to challenging conditions and its wide range of uses, bhimal can enhance both economic and environmental outcomes, ensuring a more resilient and prosperous future for the Himalayan farmers.